Vorticity and intrinsic ambipolarity in turbulent tokamaks - Parra, F; Catto, P (2009)
Traditional electrostatic gyrokinetic treatments consist of a gyrokinetic Fokker-Planck equation and a gyrokinetic quasineutrality equation. Both of these equations can be found up to second order in a gyroradius over macroscopic length expansion in some simplified cases, but the versions implemented in codes are typically only first order. In axisymmetric configurations such as the tokamak, the accuracy to which the distribution function is calculated is insufficient to determine the neoclassical radial electric field. Moreover, we prove here that turbulence dominated tokamaks are intrinsically ambipolar, as are neoclassical tokamaks. Therefore, traditional gyrokinetic descriptions are unable to correctly calculate the toroidal rotation and hence the axisymmetric radial electric field. We study the vorticity equation, ∇ J = 0, in the gyrokinetic regime, with wavelengths on the order of the ion Larmor radius. We explicitly show that gyrokinetics needs to be calculated at least to third order in the gyroradius expansion if the radial electric field is to be retrieved from quasineutrality. The method employed to study the vorticity equation also suggests a solution to the problem, namely, solving a gyrokinetic vorticity equation instead of the quasineutrality equation. The vorticity equations derived here only obtain the potential within a flux function as required. © 2009 IOP Publishing Ltd.